Charge Carrier Dynamics in Sn-Doped Two-Dimensional Lead Halide Perovskites Studied by Terahertz Spectroscopy - Qin, Zhengyuan; Zhang, Chunfeng; Chen, Lan; Wang, Xiaoyong; Xiao, Min (Frontiers in Energy Research, 2021)
Sn doping is established as an effective approach to promote the light emission properties in in two-dimensional lead-halide perovskites. However, the effect on the charge carrier dynamics is largely unexplored. In this work, we conduct terahertz spectroscopy to study the effects of Sn doping on the charge dynamics in the two-dimensional perovskites PEA2SnxPb1–xI4 (PEA = phenethylammonium) with different doping levels. The spectral dispersion analysis suggests that the early-stage dynamics with lifetime of ∼ 2 ps is contributed by both the transport of hot charge carriers and the polarizability of hot excitons. The long-lived component of first-order charge carrier recombination is dramatically improved when Sn doping increases, which is ascribed to the equilibrium between charge carriers and excitons with smaller bind energies in the higher-level Sn-doped samples. The finding in this work suggests Sn doping is an effective approach to optimize the charge carrier transport in 2D perovskite for potential optoelectronic applications.